Non-coding murine centromeric transcripts associate with and potentiate Aurora B kinase - Ferri, Federica (Oxford University Press, 2009)
Non-coding RNAs are emerging as key players in many fundamental biological processes, including specification of higher-order chromatin structure. We examined the implication of RNA transcribed from mouse centromeric minor satellite repeats in the formation and function of centromere-associated complexes. Here we show that the levels of minor satellite RNA vary during cell-cycle progression, peaking in G2/M phase, concomitant with accumulation of proteins of the chromosomal passenger complex near the centromere. Consistent with this, we describe that murine minor satellite RNA are components of CENP-A-associated centromeric fractions and associate with proteins of the chromosomal passenger complex Aurora B and Survivin at the onset of mitosis. Interactions of endogenous Aurora B with CENP-A and Survivin are sensitive to RNaseA. Likewise, the kinase activity of Aurora B requires an RNA component. More importantly, Aurora B kinase activity can be potentiated by minor satellite RNA. In addition, decreased Aurora B activity after RNA depletion can be specifically rescued by restitution of these transcripts. Together, our data provide new functional evidence for minor satellite transcripts as key partners and regulators of the mitotic kinase Aurora B.